Low host specificity of beetles associated with fruit falls in lowland tropical rainforest of north‐east Australia. Issue 1 (29th August 2013) - Grimbacher, Peter S; Nichols, Cassandra; Wardhaugh, Carl W; Stork, Nigel E
Abstract Most host‐specificity studies of tropical rainforest insects have focused on those species feeding on leaves. Apart from the fruit flies, the level of specialisation among fruit‐associated insects is poorly known. The relative contribution to local species richness made by insects feeding or associated with fallen fruits is also unknown. Beetles from fruit falls over a 5‐year period in lowland tropical rainforest at Cape Tribulation, Australia were sampled. A total of 5157 individual beetles of 73 species were sampled from the fruits of 18 different plant species. Only a few species were of frugivorous families, and most species are likely utilising resources associated with the breakdown of the fruits. The size of the fruit fall‐associated beetle assemblage (73 spp) was small compared with the number of species collected during a 4‐year sampling program conducted at the same site prior to the current study using 10 combined Malaise‐Flight Interception Traps (1473 spp, 77 families). The number of beetles and species collected from fruit that were very strongly correlated with the number of times fruit falls from a particular species of plant were sampled. The locally common palm, Normanbya normanbyi, produced fruit throughout the year and supported the largest number of fruit‐associated species. It is suggested that this might be a keystone resource for local fruit fall‐associated insect species. Although most beetle species showed a preference for the fruits of a particular plant species, overall host specificity for beetles was low. This is probably because fruit resources at this site are spatially and temporally patchy. Our results challenge the notion that most insects associated with fruit falls in tropical rainforests are highly host‐specific.